The role of universities and schools in countering and preventing violent extremism: Malaysian experience - Muhammad Uthman El-Muhammady, Ahmad El-Muhammady (Rajaratnam School of International Studies and Konrad Adenauer Stiftung, 2018)
This essay explores the roles of universities and schools in dealing with the violent extremism phenomenon in Malaysia. In doing so, the article is divided into three parts: firstly, it discusses the recent involvement of lec- turers and students in supporting pro-Daesh movements in Malaysia. The second part deals with the question of why universities and schools are be- ing targeted as recruitment grounds. The third part of the essay explores the roles of universities and schools in tackling violent extremism among their communities. The author asserts that universities and schools have a unique function in society to curb the rise of violent extremism. However, these functions are currently undercapitalised and not fully utilised to the optimum level, at least in the Malaysian context. Educational institutions are considered to be “the third force” in countering violent extremism and terrorism, alongside government agencies and the intelligence community. They have multiples roles such as detector, educator, preventer, and pro- ducer of ideas in countering violent extremism.